Single dose combination nanovaccine provides protection against influenza A virus in young and aged mice. (21st January 2019) - Ross, Kathleen; Senapati, Sujata; Alley, Jessica; Darling, Ross; Goodman, Jonathan; Jefferson, Matthew; Uz, Metin; Guo, Baoqing; Yoon, Kyoung-Jin; Verhoeven, David; Kohut, Marian; Mallapragada, Surya; et al.
Abstract : Combined polyanhydride nanoparticles and pentablock copolymer micelles provide protection against homologous challenge in aged mice. Abstract : Immunosenescence poses a formidable challenge in designing effective influenza vaccines for aging populations. While approved vaccines against influenza viruses exist, their efficacy in older adults is significantly decreased due to the diminished capabilities of innate and adaptive immune responses. In this work, the ability of a combination nanovaccine containing both recombinant hemagglutinin and nucleoprotein to provide protection against seasonal influenza virus infection was examined in young and aged mice. Vaccine formulations combining two nanoadjuvants, polyanhydride nanoparticles and pentablock copolymer micelles, were shown to enhance protection against challenge compared to each adjuvant alone in young mice. Nanoparticles were shown to enhance in vitro activation of dendritic cells isolated from aged mice, while both nanoadjuvants did not induce proinflammatory cytokine secretion which may be detrimental in aged individuals. In addition, the combination nanovaccine platform was shown to induce demonstrable antibody titers in both young and aged mice that correlated with the maintenance of body weight post-challenge. Collectively, these data demonstrate that the combination nanovaccine platform is a promising technology for influenza vaccines for older adults.